Ultrasonographic features of the uterus and ovaries in Holstein-Sahiwal crossbred dairy heifers at different phases of the estrous cycle - Ponco, Kristine Ysabel Y.; Pajas, Arville Mar Gregorio A.; Rayos, Antonio A. (2021)
The ultrasound features of the uterus, ovaries, dominant follicles, and corpora lutea of crossbred dairy heifers were described in relation to the phases of the estrous cycle. Ten (10) Holstein-Sahiwal crossbred dairy heifers underwent a double injection synchronization program using Prostaglandin F2α, and sonograms of the uterus, ovaries, and its related structures (dominant follicles and corpora lutea) were obtained at each phase of the estrous cycle: estrus, metestrus, diestrus, and proestrus. B-mode sonograms were collected using an ultrasound machine equipped with a 7.5 MHz transrectal linear array scanner. Significantly higher measurements in the thickness of the left uterine horn were observed, revealing a thicker hyperechoic uterine wall during estrus in contrast to metestrus. The left uterine horn wall was significantly thicker during proestrus and thinnest during metestrus and diestrus. The ovaries appeared as a heterogeneously hypoechoic structure with the right ovary during proestrus having a significantly lower echo score, appearing less echogenic in contrast to other phases. The ovoid anechoic follicles at proestrus and estrus revealed lower echo scores than the hypoechoic corpus luteum at diestrus. The results of this study can serve as baseline information for further studies to improve reproductive performance in dairy heifers.
Keywords: Veterinary ultrasonography; Heifers